HUBUNGAN KARAKTERISTIK PERAWAT DENGAN PENANGANAN PERTAMA PADA PASIEN KEGAWATAN MUSKULOSKELETAL DI RSUP Prof. Dr. R. D. KANDOU MANADO - Mawu, Daniel Piter; Bidjuni, Hendro; Hamel, Rivelino (JURNAL KEPERAWATAN, 2016)
Abstract: characteristics are the trait of each individual first aid treatment is emergency aid or treatment given to someone injured accurately and quickly. Aim of the study: is to identify the relationship between nurse’s characteristic (age, gender, level of education, years of service) and first aid treatment of musculoskeletal emergency patient. Methods: design of this study using analytic survey with cross sectional approach. The population are all nurses who work at Trauma Emergency Department and Triage Resuscitation Room on Emergency Department in Prof. Dr. D. R. Kandou Manado Hospital and using total sampling technique that involved 47 nurses. The tools that used in this study are questionnaires. Result: analysis was using chi-square test with a significance level of 95% (ɑ = 0,05) shows that the p value is 0.094 for age, p=0.703 for gender, p=1.000 for lever of education, p=0.001 for years of service. Conclusion: there are no relationship between age, gender, level of education with first aid treatment of musculoskeletal emergency patient. There is a relationship between years of service and first aid treatment of musculoskeletal emergency patient at Emergency Department in Prof. Dr. D. R. Kandou Manado Hospital Recommendations: for nurses to pay more attention to the quality of emergency care in first aid treatment. Training program needs to be held to keep the professional service. Keywords: nurse’s characteristic, first aid treatment. Abstrak: Karakteristik adalah ciri-ciri dari setiap individu. Penanganan pertolongan pertama adalah pemberian pertolongan secara cepat dan tepat. Tujuan Penelitian: Mengetahui hubungan karakteristik perawat (umur, jenis kelamin, tingkat pendidikan, dan masa kerja) dengan penanganan pertolongan pertama pada pasien kegawatan muskuloskeletal. Metode: menggunakan desain penelitian survey analitik dengan pendekatan cross sectional. Populasi adalah seluruh perawat yang ada di instalasi gawat darurat RSUP. Prof. DR. R. D. Kandou Manando di ruangan Triase, Resusitasi dan IRDB. Teknik pengambilan sampel menggunakan total sampling dengan jumlah 47 sampel. Pengumpulan data menggunakan kuesioner. Hasil: hasil analisis menggunakan chi-square dengan tingkat kemaknaan 95% (α=0.05) didapatkan nilai p=0.094 untuk umur, p=0.703 untuk jenis kelamin, p=1.000 untuk tingkat pendidikan, dan p=0.001 untuk masa kerja. Simpulan: tidak terdapat hubungan antara umur, jenis kelamin, dan tingkat pendidikan dengan penanganan pertolongan pertama pada pasien kegawatan muskuloskeletal. Terdapat hubungan antara masa kerja dengan penanganan pertolongan pertama pada pasien kegawatan muskuloskeletal di Instalasi Gawat Darurat RSUP Prof. Dr. R. D. Kandou Manado. Saran: bagi perawat lebih pertahankan kualitas pelayanan kegawatdaruratan dalam penanganan pertolongan pertama. Perlu di adakan program pelatihan penanganan pertolongan pertama agar tetap terajaga pelayanan yang profesional. Kata Kunci : Karakteristik Perawat, Penanganan Pertolongan Pertama